2006
DOI: 10.3201/eid1212.060732
|View full text |Cite
|
Sign up to set email alerts
|

Foodborne Transmission of Nipah Virus, Bangladesh

Abstract: TOC summary line: Nipah virus was likely transmitted from fruit bats to humans by drinking fresh date palm sap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
342
0
16

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 425 publications
(359 citation statements)
references
References 18 publications
1
342
0
16
Order By: Relevance
“…This extended survival time may have contributed to the NiV outbreak in Tangail, Bangladesh in 2005 where there was a strong epidemiological link between human NiV cases and drinking raw date palm sap (16). Fruit bats are known to drink from the pots in which the sap is collected and fruit bat excrement in or on the pots is sometimes observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This extended survival time may have contributed to the NiV outbreak in Tangail, Bangladesh in 2005 where there was a strong epidemiological link between human NiV cases and drinking raw date palm sap (16). Fruit bats are known to drink from the pots in which the sap is collected and fruit bat excrement in or on the pots is sometimes observed.…”
Section: Discussionmentioning
confidence: 99%
“…The pigs were probably infected by P. vampyrus bats that fed on fruit trees adjacent to the pig farms, either through direct exposure to urine or via saliva-contaminated partially eaten fruit dropped into the pigsties (4). In the Tangail outbreak, NiV transmission to humans apparently occurred via date palm sap (15,16). The sap may have been contaminated by urine, faeces or saliva from P. giganteus which are known to feed on the sap during harvesting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, in addition to these countries, the virus has been detected in fruit bats or the bats were seropsitive to NiV antibodies from Cambodia [79], Thailand [90], Indonesia [81], India [23,99], Madagascar in Southern Africa [41] and Ghana in West Africa [22,37]. P. giganteus is the only Pteropus species present in Bangladesh [59]. In the Naogaon (Bangladesh) investigation, 2 of 19 P. giganteus specimens had antibody against NiV.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…Fruit bats (P. giganteus) are a nuisance to date palm sap collectors because the bats drink the sap at night from the clay pots used to collect the sap. The investigations by Luby et al [59] suggested that NiV was transmitted from P. giganteus to persons through drinking fresh date palm sap. Date palm sap is a national delicacy that is enjoyed by millions of Bangladeshis each winter.…”
Section: The Transmission Route Of Nipah Virusmentioning
confidence: 99%